2021
DOI: 10.1038/s41598-021-97470-6
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular myocardial oxygen tension is reduced in monocrotaline-induced pulmonary hypertension in the rat and restored by myo-inositol trispyrophosphate

Abstract: Pulmonary hypertension (PH) initially results in compensatory right ventricular (RV) hypertrophy, but eventually in RV failure. This transition is poorly understood, but may be triggered by hypoxia. Measurements of RV oxygen tension (pO2) in PH are lacking. We hypothesized that RV hypoxia occurs in monocrotaline-induced PH in rats and that myo-inositol trispyrophosphate (ITPP), facilitating oxygen dissociation from hemoglobin, can relieve it. Rats received monocrotaline (PH) or saline (control) and 24 days lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The PH animals also showed increased rates of rise (dP/dt max ) and decrease (dP/dt min ) of right ventricular pressure. These data suggest that in our model RV maintains its function by increasing contractile (inotropic) and lusitropic action and is still in a compensatory phase (Vélez-Rendón et al, 2018;Oknińska et al, 2021). In addition, the histopathological results support functional and organ hypertrophic changes in RV.…”
Section: Induction Of Pulmonary Hypertensionsupporting
confidence: 69%
“…The PH animals also showed increased rates of rise (dP/dt max ) and decrease (dP/dt min ) of right ventricular pressure. These data suggest that in our model RV maintains its function by increasing contractile (inotropic) and lusitropic action and is still in a compensatory phase (Vélez-Rendón et al, 2018;Oknińska et al, 2021). In addition, the histopathological results support functional and organ hypertrophic changes in RV.…”
Section: Induction Of Pulmonary Hypertensionsupporting
confidence: 69%
“…It is accompanied by RV failure, as evidenced by reduced RV contractility, RV dilation and ventricular–arterial uncoupling due to both increased Ea (caused by increased PVR) and reduced contractility; however, the increase in RV Ea was quite mild (approx. 30%) as compared to that in the models of monocrotaline-induced pulmonary hypertension and pulmonary artery banding, where three–five-fold increases were found [ 26 , 27 ]. Model RV is able to generate much higher systolic pressures and typically initially goes through the phase of at least a temporary compensatory increase in contractility, decompensating when Ea is increased by many fold, at much higher afterloads.…”
Section: Discussionmentioning
confidence: 99%
“…We exclude experimentally induced hypoxia during the efficiency determination as a cause of reduced work. However, myocyte hypoxia cannot be excluded in hypertrophied RV myocardium in vivo (Oknińska et al 2021). The positive correlation of work and efficiency may suggest that inotropic intervention improves both cardiac output and efficiency.…”
Section: Determinants Of Workmentioning
confidence: 96%
“…Oxidative metabolism can limit ATP production either by hypoxia (Oknińska et al 2021) or otherwise (Balestra et al 2015;Fowler et al 2019;Koop et al 2019). It has been demonstrated that hypoxia-inducible transcription factor (HIF)-1a is upregulated in hypertrophied right ventricular cardiomyocytes (des Tombe et al 2002;Simonides et al 2008;Sutendra et al 2013), complex I of the electron transport chain is inhibited (Wüst et al 2016) and complex II becomes a source of reactive oxygen species (Redout et al 2007).…”
Section: Introductionmentioning
confidence: 99%